Computer-Based Reading Texts to Support Fourth Graders’ Reading Comprehension (GIST – Education and Learning Research Journal, 2020)
In an experimental research design, elementary school fourth grade students (n = 60) were randomly assigned to either computer-based reading or traditional reading conditions in this study. The groups completed before-reading, during-reading and after-reading activities on computer or in traditional format, respectively. The computer-based reading texts included static and animated visuals and background sounds. Students in each group completed a pretest, four reading texts and a posttest over a six-week period: the pretest in the first week, the four texts in the following four weeks, and the posttest in the sixth week. The results showed that although no significant difference was found between group’s pretest scores, computer-based group has significantly better posttest scores than the traditional group. Additionally, the fourth graders in the computer-based reading group significantly improved their reading comprehension. However, there was no significant difference between students’ reading comprehension results from pretest to posttest in traditional group. As a result, presenting students multimedia supported reading activities has a positive impact on their reading comprehension. Thus, we recommend teachers use individual and visually-supported computer-based reading texts to improve students’ reading comprehension.
Keywords: Reading Comprehension; Elementary Education; Fourth Graders; Computer-Based Reading; Animated Visuals